Penggunaan Umpatan pada Siswa Sekolah Dasar di Kudus - Satiti, Sabbihisma Debby; Ma’shumah, Nadia Khumairo (Jurusan Bahasa dan Sastra Jawa Universitas Negeri Semarang, 2021)
Swearing is not only uttered by adults, but also by children. This study seeks to examine the swear words uttered by elementary school students. This study aims to describe the forms and references of swear word uttered by elementary school students. This study used a qualitative and quantitative approach with a case study model because it only used 10 elementary school students as data sources who were selected using purposive sampling technique. The data of this research are respondents' utterances that contain swear words. Data obtained by the method of observation, interviews and note taking techniques. Data analysis used analytical descriptive techniques. The results showed that the swear words produced by elementary school students in Kudus consisted of words and phrases. The type of swear word that is produced is original form and swear words that are smoothed. The swear words derive from: 1) the name of the animal; 2) body parts; 3) circumstances; 4) inanimate objects; and 5) activities. In addition, there are differences in swearing preferences in terms of gender. Female students tended to use swear words that are smoothed out, while male students tended to use swear words in their original form. Keywords: reference, elementary school, students, swear words